Bridging the implementation and information gap on cancer prevention and survivorship in Europe: results from the iPAAC Joint Action. (30th September 2020) - De Angelis, R; Lipponen, S
Abstract: Background: About 40% of cancers are preventable and of those cancers about 50% are due to tobacco. Cancer prevention and early detection can reduce remarkably cancer burden and inequalities with effective strategies from the European Code Against Cancer. A better use of registries data can help to bridge the existing information gaps on cancer survivors, a dramatically growing population challenging the sustainability of public health systems in Europe. Methods: Policy implementation through collaborative efforts based on cancer registry data, comprehensive policies and innovations. Promotion of standards and methods to facilitate systematic delivery of comparable indicators on cancer survivors by country in Europe. Results: In cancer prevention known effective measures require European-wide comprehensive action. Population-based cancer screening programmes need continuous quality assurance and follow-up. Prevalence of short- and long-term survivors derived from a joint European dataset (EUROCARE-6, 29 countries) show that differences in survivorship are wide, consistently with demography, incidence and survival patterns. Breast, colorectal and prostatic cancers are the most frequent among all cancer survivors. Conclusions: Collaboration across fields of science and policy sectors is needed to boost cancer prevention. Cancer survivors are a growing heterogeneous population to be monitored in public health to support Health Technology Assessment and survivors' care planning. Key messages: Priority actions are developed within iPAAC Joint Action to encourage effective policies and implementation. Joint analysis of standardised European datasets strengthens the impact of cancer registries information. Indicators on cancer prevalence should be systematically integrated in the European Cancer Information System (ECIS).